A kind of quartz stone plate and preparation method thereof
By combining the modified quartz powder and the resin system, an interpenetrating network structure is formed, which solves the problem of excessive resin consumption in artificial quartz stone, and achieves the effect of reducing production costs and improving aging resistance.
Patent Information
- Application Number
- CN202411597234.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The amount of resin used in existing artificial quartz stones is too large, resulting in high production costs and reduced yellowing resistance. The solid waste treatment after the resin is cured is difficult, causing secondary pollution in the environment.
By using modified quartz powder, combined with unsaturated polyether and whitening agent, the surface of the quartz powder is lipophilic, improving its compatibility and dispersion in the resin, and passing through a crosslinking agent Form an interpenetrating network structure to improve the strength and aging resistance of quartz stone slabs.
It reduces the use of resin in quartz stone slabs, reduces production costs, and improves the aging resistance and strength of the sheets, reducing environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz stone plates, and in particular to a quartz stone plate and a preparation method thereof. Background Art
[0002] In the artificial stone industry, resin costs account for about 55% to 80% of the entire artificial stone production cost. Unsaturated resin uses styrene as the main solvent. Styrene and other organic substances volatilize during the production process, affecting the environment and the health of production workers. Excessive use of resin can lead to a decrease in the yellowing resistance of the board. In addition, the unsaturated resin used in organic artificial quartz stone is a petrochemical product and a non-renewable resource. It is difficult to treat the solid waste after the resin is solidified, causing secondary pollution to the environment. Reducing the amount of resin is crucial to controlling the production cost of artificial stone.
[0003] At present, there are two methods to reduce the amount of resin: powder modification and aggregate grading. Research on reducing the amount of resin from the perspective of powder modification has begun to be taken seriously by the industry. As a mineral filler, the direct application of quartz powder in the field of organic artificial quartz stone is not ideal. There are active silanol groups and adsorbed water on the surface of quartz powder, which makes the surface hydrophilic and oleophobic, and has poor affinity with resin. It is difficult to infiltrate and disperse in non-polar resins. When applied to artificial stone systems, it will be unevenly dispersed and aggregated, and the amount of resin will increase, and the production cost will remain high. By modifying the surface of quartz powder with a modifier under a specific process, the problems of powder agglomeration and uneven dispersion can be improved, and the dual effects of reducing the amount of resin and reducing costs and improving the performance of the board can be achieved. It has broad application prospects in the organic artificial quartz stone industry and has a positive significance for promoting green environmental protection directions such as national resource conservation and low-carbon economic development.
[0004] In view of this, this invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a quartz stone plate which requires a low amount of resin and has excellent aging resistance and strength properties.
[0006] The second object of the present invention is to provide a method for preparing a quartz stone plate, which has simple steps and low cost, and improves the aging resistance and strength of the quartz stone plate while reducing the amount of resin used.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a quartz stone plate, comprising the following raw materials in parts by mass:
[0009] 60-100 parts of quartz sand, 20-40 parts of modified quartz powder, 10-20 parts of unsaturated resin, 0.08-1 parts of curing agent, 0.03-0.1 parts of reducing agent, 0.01-0.05 parts of initiator and 0.01-0.1 parts of cross-linking agent;
[0010] The modified quartz powder comprises quartz powder and a modifier attached to the surface of the quartz powder, wherein the modifier comprises an unsaturated polyether and a whitening agent.
[0011] Furthermore, the general structural formula of the unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2) n OH; wherein n is an integer greater than 0, and R is selected from any one of C1 to C4 alkyl groups;
[0012] And / or, the brightener comprises brightener CBS-X, and the main component of the brightener CBS-X is 4,4'-bis(2-sodium sulfonate styryl)biphenyl.
[0013] Furthermore, the mass ratio of the unsaturated polyether to the brightener is (20-40): (0.1-3).
[0014] Furthermore, the quartz sand, calculated by weight, includes: 40 to 60 parts of quartz sand with a particle size of 40 to 70 meshes and 20 to 40 parts of quartz sand with a particle size of 70 to 120 meshes.
[0015] Furthermore, the particle size of the modified quartz powder is 300-350 mesh.
[0016] Furthermore, the cross-linking agent includes at least one of divinylbenzene, N,N-methylenebisacrylamide and isocyanate.
[0017] Further, the initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide and ammonium persulfate;
[0018] And / or, the reducing agent comprises ascorbic acid.
[0019] Further, the curing agent includes methyl ethyl ketone peroxide;
[0020] And / or, the unsaturated resin includes orthophthalic unsaturated polyester resin and / or isophthalic unsaturated polyester resin.
[0021] In a second aspect, the present invention also provides a method for preparing the quartz stone plate as described above, comprising the following steps:
[0022] After the raw materials are mixed, pressed and solidified, the quartz stone plate is obtained.
[0023] Furthermore, the curing temperature is 40-50°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The quartz stone plate of the present invention reduces the amount of resin and reduces the cost by adding modified quartz powder while ensuring the material state and product quality; under the action of the crosslinking agent, the unsaturated bonds in the surface active groups of the modified quartz powder react with the unsaturated resin system to form an interpenetrating network structure, thereby improving the strength and aging resistance of the quartz stone plate. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] A quartz stone plate and a preparation method thereof according to an embodiment of the present invention are described in detail below.
[0028] In some embodiments of the present invention, a quartz stone plate is provided, which comprises the following raw materials in parts by mass:
[0029] 60-100 parts of quartz sand, 20-40 parts of modified quartz powder, 10-20 parts of unsaturated resin, 0.08-1 parts of curing agent, 0.03-0.1 parts of reducing agent, 0.01-0.05 parts of initiator and 0.01-0.1 parts of cross-linking agent;
[0030] The modified quartz powder comprises quartz powder and a modifier attached to the surface of the quartz powder, wherein the modifier comprises an unsaturated polyether and a whitening agent.
[0031] The surface of quartz as a mineral filler has active silanol groups and adsorbed water, resulting in a hydrophilic and oleophobic surface. The present invention uses unsaturated polyether for modification, so that the surface of quartz powder is combined with the hydroxyl group of the unsaturated polyether, and the surface of the quartz powder is coated with small molecules of polyether, presenting an oleophilic state, improving the surface polarity, thereby improving the compatibility, dispersibility and stability of the quartz powder in the organic matrix; at the same time, the addition of a whitening agent can improve the whiteness of the modified quartz powder; adding the above-mentioned modified quartz powder to a quartz stone plate can significantly reduce the amount of unsaturated resin used in the quartz stone plate; at the same time, under the action of a cross-linking agent, the unsaturated bonds in the surface active groups of the modified quartz powder react with the unsaturated resin system to form an interpenetrating network structure, thereby improving the strength and aging resistance of the quartz stone plate.
[0032] In different embodiments of the present invention, the mass fraction of quartz sand in the raw material of the quartz stone plate can be 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or a range of any two parts thereof;
[0033] The mass fraction of the modified quartz powder can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or a range consisting of any two of them;
[0034] The mass fraction of the unsaturated resin may be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts or a range consisting of any two of them;
[0035] The mass fraction of the curing agent can be 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 part or a range consisting of any two of them;
[0036] The mass fraction of the reducing agent may be 0.03, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range consisting of any two of them;
[0037] The mass fraction of the initiator can be 0.01 part, 0.02 part, 0.03 part, 0.04 part, 0.05 part or a range consisting of any two of them;
[0038] The mass fraction of the cross-linking agent can be 0.01 part, 0.02 part, 0.04 part, 0.06 part, 0.08 part, 0.1 part or a range consisting of any two of them.
[0039] In some embodiments of the present invention, the general structural formula of the unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2)n OH; wherein n is an integer greater than 0, and R is selected from any one of C1~C4 alkyl groups.
[0040] The unsaturated polyether molecules of the present invention contain vinyl groups, which react with the unsaturated bonds of the unsaturated resin under the action of an initiator and a curing agent to form an interpenetrating network structure, thereby facilitating the improvement of the strength and aging resistance of the quartz stone plate.
[0041] In some embodiments of the present invention, the unsaturated polyether includes at least one of allyl polyoxyethylene ether, methyl allyl polyoxyethylene ether, isopentanol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene alcohol ether, ethylene glycol monovinyl polyoxyethylene glycol ether and 4-hydroxybutyl vinyl polyoxyethylene ether; preferably, the molecular weight of the unsaturated polyether is 1000~3000.
[0042] In some embodiments of the present invention, the whitening agent includes but is not limited to whitening agent CBS-X, and the main component of whitening agent CBS-X is 4,4'-bis(2-sodium sulfonate styryl)biphenyl.
[0043] In some embodiments of the present invention, the mass ratio of the unsaturated polyether to the brightener is (20-40): (0.1-3); typically but not limiting, for example, the mass ratio of the unsaturated polyether to the brightener can be 20:0.1, 20:0.5, 30:1, 40:3 or a range of any two thereof; preferably, the mass ratio of the unsaturated polyether to the brightener is (20-40): (0.5-1).
[0044] In some embodiments of the present invention, the method for preparing modified quartz powder comprises the following steps:
[0045] The unsaturated polyether, the brightener and water are mixed to obtain a modifier aqueous solution; the modifier aqueous solution is pumped by a metering pump, and is evenly dripped onto the surface of the quartz sand on the conveyor belt through a T-shaped porous tube, and then transported to a premixer for mixing, and then enters a ball mill for ball milling at 80-90° C. for 6-10 minutes, and modified quartz powder is obtained after air separation; preferably, the mass ratio of the unsaturated polyether, the brightener and the water is (20-40): (0.1-3): (57-79.5), and the mass of the modifier aqueous solution is 0.1%-1% of the mass of the quartz sand.
[0046] In some embodiments of the present invention, among the raw materials of the quartz stone slab, the quartz sand, calculated by weight, includes: 40 to 60 parts of quartz sand with a particle size of 40 to 70 meshes and 20 to 40 parts of quartz sand with a particle size of 70 to 120 meshes; typically but not limitatively, for example, the mass fraction of quartz sand with a particle size of 40 to 70 meshes can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or a range value consisting of any two thereof; the mass fraction of quartz sand with a particle size of 70 to 120 meshes can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or a range value consisting of any two thereof.
[0047] In some embodiments of the present invention, the particle size of the modified quartz powder is 300-350 mesh; preferably, the particle size of the modified quartz powder is 325 mesh.
[0048] In some embodiments of the present invention, the quartz stone plate includes the following raw materials in parts by mass:
[0049] 40-60 parts of quartz sand with a particle size of 40-70 mesh, 20-40 parts of quartz sand with a particle size of 70-120 mesh, 20-40 parts of modified quartz powder with a particle size of 325 mesh, 10-20 parts of unsaturated resin, 0.08-1 part of curing agent, 0.03-0.1 part of reducing agent, 0.01-0.05 part of initiator and 0.01-0.1 part of cross-linking agent.
[0050] In some embodiments of the present invention, the crosslinking agent includes at least one of divinylbenzene, N,N-methylenebisacrylamide and isocyanate.
[0051] In some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide, and ammonium persulfate.
[0052] The present invention adopts the above-mentioned medium-temperature initiator, which can make the system react at 40-50° C., thereby reducing the impact of high-temperature curing on product quality and reducing energy consumption.
[0053] In some embodiments of the invention, reducing agents include, but are not limited to, ascorbic acid.
[0054] In some embodiments of the present invention, the curing agent includes but is not limited to methyl ethyl ketone peroxide.
[0055] In some embodiments of the present invention, the unsaturated resin includes an orthophthalic unsaturated polyester resin and / or an isophthalic unsaturated polyester resin.
[0056] In some embodiments of the present invention, a method for preparing the above-mentioned quartz stone plate is also provided, comprising the following steps:
[0057] After the raw materials are mixed, pressed and solidified, a quartz stone slab is obtained.
[0058] The preparation method of the quartz stone plate of the present invention is simple to operate and low in cost. Without changing the existing grinding process and the production process of the quartz stone plate, the amount of resin can be reduced and the aging resistance and strength of the quartz stone plate can be improved.
[0059] In some specific embodiments of the present invention, pressing includes using a press, and the parameters of the press are: vibration frequency of 250 Hz, vacuum degree of 0.75 bar, and pressure of 2 MPa.
[0060] In some embodiments of the present invention, the curing temperature is 40-50° C.; typically but not limiting, for example, the curing temperature may be 40° C., 45° C., 50° C. or a range of any two thereof.
[0061] In some embodiments of the present invention, the method for preparing the quartz stone plate specifically comprises the following steps:
[0062] After mixing quartz sand and modified quartz powder in a blender, add unsaturated resin, curing agent, reducing agent, initiator and cross-linking agent and mix until the material is in a state that can be pressed into shape; use a spreading machine to evenly spread the material in the mold, vacuum, vibrate, and press the material into shape, and then cure it at 40-50°C for 2-3h, and then remove the mold, cut the edges, and grind the surface to 3000 mesh in turn to obtain a quartz stone slab.
[0063] Example 1
[0064] The quartz stone plate provided in this embodiment includes the following raw materials in parts by mass:
[0065] 40 parts of quartz sand with a particle size of 40-70 mesh, 20 parts of quartz sand with a particle size of 70-120 mesh, 27 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of o-phthalic unsaturated polyester resin, 0.8 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid), 0.05 parts of initiator (ammonium persulfate) and 0.1 parts of cross-linking agent (N,N-methylenebisacrylamide);
[0066] The preparation method of modified quartz powder comprises the following steps:
[0067] Methyl allyl polyoxyethylene ether, brightener CBS-X (main component is 4,4'-bis(2-sodium sulfonate styrene) biphenyl) and water are mixed in a mass ratio of 0.3:0.01:0.69 to obtain a modifier aqueous solution; the modifier aqueous solution is pumped by a metering pump and evenly dripped onto the surface of quartz sand (particle size is 40-120 mesh) on the conveyor belt through a T-shaped porous tube. The mass of the modifier aqueous solution is 0.3% of the mass of the quartz sand. The modifier is then transported to a premixer for mixing and then enters a ball mill for ball milling at 85°C for 8 minutes. After air separation, modified quartz powder with a particle size of 325 mesh is obtained.
[0068] The method for preparing the quartz stone plate provided in this embodiment comprises the following steps:
[0069] After adding quartz sand with a particle size of 40-70 mesh, quartz sand with a particle size of 70-120 mesh and modified quartz powder with a particle size of 325 mesh into a vertical mixer and stirring for 3-5 minutes, a mixture of orthophthalic unsaturated polyester resin (half of the total amount), curing agent and initiator is added into the mixer and stirred for 3-5 minutes, and then the remaining orthophthalic unsaturated polyester resin, reducing agent and cross-linking agent are added and stirred for 5 minutes; the material is evenly distributed in the mold by a distribution machine, and the material is vacuumed, vibrated and pressed into shape (the parameters of the press are: vibration frequency of 250Hz, vacuum degree of 0.75bar, pressure of 2MPa), and then cured at 40-50℃ for 2-3h, and the mold is removed, the edge is cut, and the surface is polished to 3000 mesh in turn to obtain a quartz stone plate.
[0070] Example 2
[0071] The quartz stone plate provided in this embodiment includes the following raw materials in parts by mass:
[0072] 45 parts of quartz sand with a particle size of 40-70 mesh, 20 parts of quartz sand with a particle size of 70-120 mesh, 22 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin, 0.87 parts of curing agent (methyl ethyl ketone peroxide), 0.04 parts of reducing agent (ascorbic acid), 0.04 parts of initiator (ammonium persulfate) and 0.05 parts of cross-linking agent (N,N-methylenebisacrylamide); wherein the modified quartz powder is the same as that in Example 1.
[0073] The preparation method of the quartz stone slab provided in this embodiment refers to Example 1.
[0074] Example 3
[0075] The quartz stone plate provided in this embodiment includes the following raw materials in parts by mass:
[0076] 42 parts of quartz sand with a particle size of 40-70 mesh, 23 parts of quartz sand with a particle size of 70-120 mesh, 23 parts of modified quartz powder with a particle size of 325 mesh, 11 parts of ortho-phthalic unsaturated polyester resin, 0.96 parts of curing agent (methyl ethyl ketone peroxide), 0.03 parts of reducing agent (ascorbic acid), 0.03 parts of initiator (ammonium persulfate) and 0.08 parts of cross-linking agent (N,N-methylenebisacrylamide); wherein the modified quartz powder is the same as that in Example 1.
[0077] The preparation method of the quartz stone slab provided in this embodiment refers to Example 1.
[0078] Example 4
[0079] The quartz stone plate provided in this embodiment includes the following raw materials in parts by mass:
[0080] 40 parts of quartz sand with a particle size of 40-70 mesh, 20 parts of quartz sand with a particle size of 70-120 mesh, 27 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin, 0.08 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid), 0.05 parts of initiator (benzoyl peroxide) and 0.1 parts of cross-linking agent (divinylbenzene); wherein the modified quartz powder is the same as that in Example 1.
[0081] The preparation method of the quartz stone slab provided in this embodiment refers to Example 1.
[0082] Example 5
[0083] The quartz stone plate provided in this embodiment includes the following raw materials in parts by mass:
[0084] 40 parts of quartz sand with a particle size of 40-70 mesh, 20 parts of quartz sand with a particle size of 70-120 mesh, 27 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin, 0.08 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid), 0.05 parts of initiator (benzoyl peroxide) and 0.1 parts of cross-linking agent (divinylbenzene); wherein, the preparation method of modified quartz powder refers to Example 1, except that methyl allyl polyoxyethylene ether is replaced by 4-hydroxybutyl vinyl polyoxyethylene ether.
[0085] The preparation method of the quartz stone slab provided in this embodiment refers to Example 1.
[0086] Comparative Example 1
[0087] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0088] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 28 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin, 0.8 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid) and 0.05 parts of initiator (ammonium persulfate); wherein the modified quartz powder is the same as that in Example 1.
[0089] The preparation method of the quartz stone slab provided in this comparative example is referenced to Example 1.
[0090] Comparative Example 2
[0091] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0092] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 25 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin and 1 part of curing agent (methyl ethyl ketone peroxide); wherein the modified quartz powder is the same as that in Example 1.
[0093] The preparation method of the quartz stone plate provided in this comparative example comprises the following steps:
[0094] After adding quartz sand with a particle size of 40-70 mesh, quartz sand with a particle size of 70-120 mesh and modified quartz powder with a particle size of 325 mesh into a vertical mixer and stirring for 3-5 minutes, a mixture of orthophthalic unsaturated polyester resin and curing agent is added into the mixer and stirred for 3-5 minutes; the material is evenly distributed in the mold by a distribution machine, and the material is vacuumed, vibrated, and pressed into shape (the parameters of the press are: vibration frequency of 250 Hz, vacuum degree of 0.75 bar, and pressure of 2 MPa), and then cured at 40-50°C for 2-3 hours, and then demolded, edge cut, and surface polished to 3000 mesh are successively performed to obtain a quartz stone plate.
[0095] Comparative Example 3
[0096] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0097] 22 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 28 parts of modified quartz powder with a particle size of 325 mesh, 12 parts of ortho-phthalic unsaturated polyester resin, 0.8 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid) and 0.05 parts of initiator (ammonium persulfate); wherein the modified quartz powder is the same as that in Example 1.
[0098] The preparation method of the quartz stone slab provided in this comparative example is referenced to Example 1.
[0099] Comparative Example 4
[0100] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0101] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 26 parts of modified quartz powder with a particle size of 325 mesh, 14 parts of ortho-phthalic unsaturated polyester resin, 0.8 parts of curing agent (methyl ethyl ketone peroxide), 0.05 parts of reducing agent (ascorbic acid) and 0.05 parts of initiator (ammonium persulfate); wherein the modified quartz powder is the same as that in Example 1.
[0102] The preparation method of the quartz stone slab provided in this comparative example is referenced to Example 1.
[0103] Comparative Example 5
[0104] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0105] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 25 parts of quartz powder with a particle size of 325 mesh, 14 parts of orthophthalic unsaturated polyester resin and 1 part of curing agent (methyl ethyl ketone peroxide).
[0106] The preparation method of the quartz stone plate provided in this comparative example comprises the following steps:
[0107] After adding quartz sand with a particle size of 40-70 mesh, quartz sand with a particle size of 70-120 mesh and quartz powder with a particle size of 325 mesh into a vertical mixer and stirring for 3-5 minutes, a mixture of orthophthalic unsaturated polyester resin and curing agent is added into the mixer and stirred for 3-5 minutes; the material is evenly distributed in the mold by a distribution machine, and the material is vacuumed, vibrated, and pressed into shape (the parameters of the press are: vibration frequency of 250Hz, vacuum degree of 0.75bar, pressure of 2MPa), and then cured at 40-50℃ for 2-3h, and then demolded, edge cut, and surface polished to 3000 mesh are obtained.
[0108] Comparative Example 6
[0109] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0110] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 25 parts of modified quartz powder with a particle size of 325 mesh, 13.5 parts of orthophthalic unsaturated polyester resin and 1 part of curing agent (methyl ethyl ketone peroxide);
[0111] The preparation method of the modified quartz powder is similar to that of Example 1, except that the silane coupling agent KH570 and water are mixed to obtain a modifying agent aqueous solution; the mass of the silane coupling agent KH570 in the modifying agent aqueous solution is 0.3% of the mass of the quartz sand.
[0112] The preparation method of the quartz stone slab provided in this comparative example refers to comparative example 5.
[0113] Comparative Example 7
[0114] The quartz stone slab provided in this comparative example includes the following raw materials in parts by mass:
[0115] 20 parts of quartz sand with a particle size of 40-70 mesh, 40 parts of quartz sand with a particle size of 70-120 mesh, 25 parts of modified quartz powder with a particle size of 325 mesh, 14 parts of orthophthalic unsaturated polyester resin and 1 part of curing agent (methyl ethyl ketone peroxide);
[0116] The preparation method of the modified quartz powder is referred to Example 1, except that the silane coupling agent KH550 and water are mixed to obtain a modifier aqueous solution; the mass of the silane coupling agent KH550 in the modifier aqueous solution is 0.3% of the mass of the quartz sand.
[0117] The preparation method of the quartz stone slab provided in this comparative example refers to comparative example 5.
[0118] Test example
[0119] The properties of the quartz stone slabs prepared in Examples 1 to 5 and Comparative Examples 1 to 7 were tested, and the results are shown in Table 1.
[0120] Resin dosage: the mass fraction of orthophthalic unsaturated polyester resin in the raw material of quartz stone plate;
[0121] Bending strength: Test standard refers to GB / T 35157-2017 "Resin-type synthetic stone slabs";
[0122] Ball impact strength and aging resistance: the test standard refers to GB / T 35157-2017 "Resin-based synthetic stone slabs";
[0123] Water absorption rate: The test standard refers to GB / T 35157-2017 "Resin-based synthetic stone slabs".
[0124] Table 1
[0125]
[0126] As can be seen from Table 1, the quartz stone plate prepared by the present invention adopts modified quartz powder, and cooperates with the initiator, reducing agent, cross-linking agent and curing agent in the resin system to form an interpenetrating network structure, which not only reduces the amount of resin, but also improves the bending strength and impact strength of the plate itself, and improves the aging resistance of the plate; reduces the preparation cost of the quartz stone plate, and reduces VOC emissions, which is in line with the low-carbon and environmental protection concept.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quartz stone plate, characterized in that: According to the weight percentage, it includes the following raw materials: 60-100 parts of quartz sand, 20-40 parts of modified quartz powder, 10-20 parts of unsaturated resin, 0.08-1 parts of curing agent, 0.03-0.1 parts of reducing agent, 0.01-0.05 parts of initiator and 0.01-0.1 parts of cross-linking agent; The modified quartz powder includes quartz powder and a modifier attached to the surface of the quartz powder, wherein the modifier includes an unsaturated polyether and a brightener; In the modified quartz powder, the mass ratio of the unsaturated polyether to the brightener is (20-40): (0.1-3); The general structural formula of the unsaturated polyether is: CH2=CH-R-(OCH2CH2) n OH, CH2=C(CH3)-R-(OCH2CH2) n OH or CH2=CH-OR-(OCH2CH2) n OH; wherein n is an integer greater than 0, and R is selected from any one of C1 to C4 alkyl groups; The cross-linking agent includes at least one of divinylbenzene, N,N-methylenebisacrylamide and isocyanate; The initiator comprises at least one of azobisisobutyronitrile, benzoyl peroxide and ammonium persulfate; The reducing agent includes ascorbic acid; The unsaturated resin includes orthophthalic unsaturated polyester resin and / or isophthalic unsaturated polyester resin.
2. The quartz stone plate according to claim 1, characterized in that: The brightener comprises brightener CBS-X, and the main component of the brightener CBS-X is 4,4'-bis(2-sodium sulfonate styryl)biphenyl.
3. The quartz stone plate according to claim 2, characterized in that: The quartz sand includes, by weight, 40 to 60 parts of quartz sand with a particle size of 40 to 70 meshes and 20 to 40 parts of quartz sand with a particle size of 70 to 120 meshes.
4. The quartz stone plate according to claim 3, characterized in that: The particle size of the modified quartz powder is 300-350 mesh.
5. The quartz stone plate according to claim 1, characterized in that: The curing agent includes methyl ethyl ketone peroxide.
6. The method for preparing the quartz stone plate according to any one of claims 1 to 5, characterized in that: The steps include: After the raw materials are mixed, pressed and solidified, the quartz stone plate is obtained.
7. The method for preparing the quartz stone plate according to claim 6, characterized in that: The curing temperature is 40-50°C.
Citation Information
Patent Citations
Interface crosslinking technology of plasma modified calcium carbonate with unsaturation resin
CN1045590A
Single-color quartz stone plate and manufacturing method
CN106810107A
Mthod of forming a filler and resin or rubber composition
GB1345475A